ANALISIS ATAS PENERAPAN PRINSIP GOOD GOVERNANCE TERHADAP PROGRAM BANTUAN STIMULAN PERUMAHAN SWADAYA PADA DINAS PERUMAHAN KAWASANPERMUKIMAN DAN PERTANAHAN KABUPATEN HALMAHERA UTARA - Nata, Inggriani; Manossoh, Hendrik; Mawikere, Lidia M. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
Good Governance is a good governance and responsible management that is divided into several principles 5 (five) including Accountability, Transparency, Ekektif and Efesien, Responsiveness, Participation. The purpose of this study To know how the implementation of the principles of Good Governance in the program Self-help stimulant assistance. In this study the data used is qualitative, while for the data source using primary and secondary data and analytical methods used are descriptive analysis method. Based on the results of the study, it was concluded that the implementation of the Good Gavernance principle in the Self-Helping Housing Stimulus Assistance Program has been well executed. Keywords: Government Accounting, Accountability, Transparency, Ekektif and Efficient, Responsiveness